Investigating Intelligence A Conversation with John Duncan. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and neuroscientist John Duncan, University of Cambridge, and examines fascinating questions in neuroscience such as: What is intelligence and what does IQ testing tell us? Can intelligence be measured and improved? What role does our frontal lobe play in executive control? John Duncan has rigorously investigated these types of issues for years and this wide-ranging conversation covers all those questions plus topics such as impairments following brain damage, functional brain imaging, and the brain basis for attention,